WHAT FACTORS DO ONLINE SHOPPERS CARE ABOUT WHEN PURCHASING? - Raudhah Raudhah; Zaki Mubarak; Rahma Yuliani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Technology is advancing. The market stays up with technical advancements. Shopee is one of the most popular online vendors today. This study aims to identify the factors that impact online shoppers' purchase decisions in the Shopee application among consumers in Banjarmasin. The quantitative methodology was employed in the research, with primary data collected via online surveys. The study's findings show that product quality and pricing partially and simultaneously impact online shoppers’ purchase decisions. The findings of this study suggest that online vendors improve the quality of their products and establish competitive rates to entice buyers to purchase.